Registration‐directed phase 1/2 trial of irinotecan for pediatric solid tumors. Issue 5 (14th May 2019) - Makimoto, Atsushi; Mugishima, Hideo; Taga, Takashi; Ishida, Yuji; Nagatoshi, Yoshihisa; Ida, Kohmei; Kumagai, Masaaki; Kimura, Toshimi; Ohashi, Yasuo; Kaneko, Michio
Abstract: Background: Although irinotecan hydrochloride (IRI) is a promising chemotherapeutic agent for pediatric solid tumors, its indications had been off‐label in the USA, EU and Japan. Therefore, we conducted a phase 1/2 trial of IRI monotherapy in a registration‐directed setting. Methods: Children aged 2–18 years with solid tumors who were either refractory to or relapsed after standard chemotherapy were enrolled. Phase 1 was a conventional dose escalation study to determine the dose‐limiting toxicity (DLT) and the recommended dose. IRI was given i.v. on days 1, 2, 3 and 8, 9, 10 in up to eight, 21 day cycles. Results: The starting dose (40 mg/m 2 /day) was determined to be the recommended dose because the next higher dose level (45 mg/m 2 /day) resulted in two cases of DLT. Seventeen children (11 in phase 1 and six in phase 2) with a refractory solid tumor received IRI. Of the 12 patients treated with 40 mg/m 2 /day, seven (58.3%) achieved a stable disease condition for >8 weeks. Conclusions: The RD of IRI in this treatment schedule was 40 mg/m 2 /day. IRI did not cause tumor shrinkage but might help to stabilize refractory pediatric solid tumors. Based on the accumulating evidence from international studies of the efficacy of IRI against refractory pediatric solid tumors, the Japanese regulatory authority approved its use for this indication in 2011.